Changes in the Structural and Functional Albumin Properties in Patients with Decompensated Liver Cirrhosis - A. A. Turkina; M. V. Maevskaya; M. S. Zharkova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to conduct a comparative analysis of serum albumin's structural and functional properties in decompensated cirrhotic patients by means of spin prob EPR spectroscopy.Materials and methods. The main study group included 70 patients with decompensated liver cirrhosis and ascites. The control group consisted of 12 healthy volunteers, comparable in gender and age, without liver diseases. To assess the structural and functional ability, serum albumin was analyzed by EPR spectroscopy.Results. Albumin levels within reference intervals were found in 37 patients (59.8 %). The native albumin index decrease in cirrhotic patients as the disease progressed with the lowest values in the Child – Pugh C group (p < 0.001). The binding efficiency of albumin decreased in accordance with the severity of cirrhosis with minimal albumin binding capacity in the Child – Pugh C (Me = 25.43 %; n = 30; p < 0.001). The transport activity of RTQ albumin decreased in patients with decompensated cirrhosis, the lowest transport ability was observed in the Child – Pugh C group (Me = 26.09 %). In patients with decompensated disease the detoxification potential was significantly reduced: Child – Pugh B — Me = 44.03 %; Child – Pugh C — Me =17.16 %. Despite the normal values of serum albumin in 72.5% of patients with cirrhosis B and in 26.7% in the cirrhosis C group, only 12.3% in the cirrhosis B group had normal albumin function and in cirrhosis C nо patients had normal albumin function.Conclusion. There were not only serum concentration depletion in cirrhotic patients, but also albumin physiological non-oncotic properties were violated. The severity of these changes increased with the progression of cirrhosis. Our data allow us to raise the question of the need to use the EPR test to determine indications for albumin replacement therapy in patients with cirrhosis and the presence of ascites, even at normal values of its serum concentration.